Proteomics in farm animals models of human diseases. Issue 10 (25th June 2014) - Ceciliani, Fabrizio; Restelli, Laura; Lecchi, Cristina
Abstract : The need to provide in vivo complex environments to understand human diseases strongly relies on the use of animal models, which traditionally include small rodents and rabbits. It is becoming increasingly evident that the few species utilised to date cannot be regarded as universal. There is a great need for new animal species that are naturally endowed with specific features relevant to human diseases. Farm animals, including pigs, cows, sheep and horses, represent a valid alternative to commonly utilised rodent models. There is an ample scope for the application of proteomic techniques in farm animals, and the establishment of several proteomic maps of plasma and tissue has clearly demonstrated that farm animals provide a disease environment that closely resembles that of human diseases. The present review offers a snapshot of how proteomic techniques have been applied to farm animals to improve their use as biomedical models. Focus will be on specific topics of biomedical research in which farm animal models have been characterised through the application of proteomic techniques.